OFDM-IM for Joint Communication and Radar-Sensing: A Promising Waveform for Dual Functionality - Şahin, Mehmet Mert; Gurol, Ilter Erol; Arslan, Emre; Basar, Ertugrul; Arslan, Huseyin (Frontiers in Communications and Networks, 2021)
The demand for dual-functional wireless systems is on the rise as certain resources become more congested and scarce. Joint communication-radar (JCR) is a promising technology that is becoming very critical and growing in popularity, where communication and radar applications are serviced simultaneously sharing the same hardware/software and the frequency band resources. JCR and its alternatives need to be cleverly integrated into certain waveforms such as orthogonal frequency division multiplexing (OFDM) to function properly without a degradation in the performance. With the aid of the promising concepts of index modulation (IM) and Golay complementary sequences, a novel JCR waveform is proposed to serve both communication and radar applications with the same resources. It has been shown by extensive computer simulations that the proposed OFDM with index modulation (OFDM-IM) waveform outperforms the classical OFDM with fixed pilot design both in bit error rate (BER) performance and radar based applications by introducing diversity among subcarriers and frequency agility over the whole frequency band.